Systemicity of Xanthomonas campestris pv. musacearum and time to disease expression after inflorescence infection in East African highland and Pisang Awak bananas in Uganda. (18th October 2012) - Ocimati, W.; Ssekiwoko, F.; Karamura, E.; Tinzaara, W.; Eden‐Green, S.; Blomme, G.
<x xml:space="preserve">Abstract</x> Banana xanthomonas wilt (XW) caused by Xanthomonas campestris pv. musacearum (Xcm) attacks all banana cultivars. Xcm in inflorescence‐infected Pisang Awak plants with wilting male bud bracts is restricted to the upper parts of the true stem; therefore, cutting these plants at the pseudostem base has been recommended to prevent further Xcm spread. In order to fine‐tune existing control strategies, this study examined the movement of Xcm into plants and mats, in relation to disease incubation period. Mature Pisang Awak and East African highland (AAA‐EA) plants were inoculated with Xcm through abscission wounds of female bracts, male bud bracts, male flowers, a combination of male bud bracts and flowers, and by cutting male buds with a contaminated machete. Thirty plants per genotype and treatment were monitored for 24 months for disease symptoms. An additional 68 AAA‐EA and 33 Pisang Awak plants were sampled weekly to assess the rate of Xcm spread within the plants. All floral entry points resulted in disease, with the highest incidence in combined male bract and male flower abscission wound inoculations. The study confirmed the systemicity of Xcm, with the pathogen able to live within the mat for long periods (5–16 months) without causing disease. Reliance on disease symptom expression to manage XW is therefore not sufficient. The long incubation period in lateral shoots may explain the current resurgence of the disease in locations where the disease was thought to have been successfully eradicated.